Hidden diversity in deep-water bandfishes: review of Owstonia with descriptions of twenty-one new species (Teleostei: Cepolidae: Owstoniinae) - Smith-Vaniz, William F.; Johnson, G. David (Zootaxa, 2016)
The bandfish family Cepolidae, comprising the subfamilies Owstoniinae and Cepolinae, is characterized, and defining characters of the three groups are identified and discussed. Characters of larvae of both subfamilies are described and illustrated. Six nominal genera of owstoniines had been proposed by various authors, but we recognize only Owstonia Tanaka. Utility of selected identification characters of the genus are discussed. Differences in lateral-line patterns have been the primary character used by some recent authors for recognition of two owstoniine genera, with Sphenanthias Weber possessing the plesiomorphic lateral-line condition. Several other patterns also occur in these fishes bringing into question the phylogenetic significance of lateral line plasticity. Sexual dimorphism in pelvic fin lengths is also present in several species. Identification keys, descriptions, synonymies, distribution maps and photographs or illustrations are provided for all Owstonia species for which adults are available.        Although only 15 valid species were previously known, a remarkable hidden diversity of these fishes was discovered in major museum collections with the following 21 species here described as new: O. ainonaka (eastern Australia), O. contodon (Philippines), O. crassa (New Caledonia and Solomon Islands), O. dispar (Solomon Islands), O. elongata (New Caledonia and Vanuatu), O. fallax (eastern Australia and New Caledonia), O. geminata (Vanuatu and Philippines), O. hastata (eastern Australia), O. hawaiiensis (Hawaiian Islands); O. ignota (Mariana Islands), O. lepiota (Tanzania), O. melanoptera (Philippines), O. merensis (eastern Australia, Torres Strait), O. mundyi (Kiribati, Christmas Island), O. nalani (eastern Australia and New Caledonia), O. nudibucca (eastern Indian Ocean, Mentawai Islands and off Myanmar), O. psilos (Western Australia), O. raredonae (Mozambique), O. rhamma (Vanuatu), O. scottensis (Western Australia, Scott Reefs) and O. similis (Madagascar). Several specimens based on small juveniles, which we describe as Owstonia sp.,  appear to be additional new species but are not formally described as such.